Chiral pool approach for the synthesis of functionalized amino acids: synthesis of antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (R)-lacosamide 1 has been achieved from N-Boc-N,O-isopropylidene-l-serinol 2 which could easily be obtained from natural l-serine. Our synthesis of 1 starting from 2 using chiral pool strategy resulted in 54% overall yield.

Clerodane type diterpene as a novel antifungal agent from polyalthia longifolia var. pendula - Bhattacharya, Asish K.; Chand, Hemender R.; John, Jyothis; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2015)
Bioactivity-guided chemical examination of methanolic extract of leaves of Polyalthia longifolia var. pendula led to the isolation of the active constituent, a diterpene 1 which was identified as 16α-hydroxycleroda-3,13(14)Z-dien-15,16-olide on the basis of its spectral data. Among the tested strains, diterpene 1 was found to exhibit antifungal activities having MIC90 values of 50.3, 100.6 and 201.2 μM against Candida albicans NCIM3557, Cryptococcus neoformans NCIM3542 (human pathogens) and Neurospora crassa NCIM870 (saprophyte), respectively. Initial, structure–activity-relationship (SAR) data generated by synthesizing some derivatives revealed that the double bond between C3–C4 and the free hydroxyl group at C16 are crucial for the antifungal activity of the diterpene 1. The mode of action of 1 in C. albicans is due to compromised cell membrane permeability and also probably due to disruption of cell wall structures. The red blood cell haemolysis of all the compounds (1–4) did not show any significant haemolysis and was found to be less than 15% for all the compounds when tested at highest concentration, i.e. 1200 μM. Interestingly, all the tested compounds inhibited Y–H transition in dimorphic C. albicans NCIM3557 at much lower concentration than their MIC90 values. Determination of ROS generation by diterpene 1 using DCFH-DA and DHR123 (dihydrorhodamine) staining of C. albicans NCIM3557 indicated production of intracellular ROS as a mechanism of antifungal activity.
Keywords: Diterpene; Polyalthia longifolia; Isolation; Flash chromatography; Natural products; Antifungal activity

Chemo-biological evaluation of antidiabetic activity of M entha arvensis L. and it's role in inhibition of advanced glycation end products - Agawane, Sachin B.; Gupta, Vidya S.; Kulkarni, Mahesh J.; Bhattacharya, Asish K.; Koratkar, Santosh (Journal of Ayurveda and integrative medicine, 2018)
Background: There has been enormous curiosity in the development of alternative plant based medicines to control diabetes, oxidative stress and related disorders. One of the therapeutic approaches is to reduce postprandial release of glucose in the blood. Two key enzymes that are involved in reducing postprandial glucose are α-amylase and α-glucosidase. Mentha arvensis L. has been traditionally used by several tribes as a medicinal plant to treat various disorders. Objective: The present study was undertaken to test M. arvenisis L. for inhibition of postprandial hyperglycemia. Material and method: We performed various in vitro and in vivo tests to evaluate efficacy of M. arvenisis L. for antidiabetic activity (postprandial hyperglycemia). Results: Methanolic extract of M. arvensis L. leaves showed DPPH free radical scavenging activity (more than 78% μg/μl) and high antiglycation potential (more than 90% inhibition of AGE formation). Methanolic extract also showed remarkable inhibitory effects on α-amylase (more than 50% μg/μl) and α-glucosidase (68% μg/μl) and significant inhibition of postprandial hyperglycemia in starch induced diabetic Wistar rats. Conclusion: The non-insulin dependent antidiabetic or inhibition of postprandial hyperglycemic activity of methanolic extract of M. arvensis L. leaves was shown by using in vitro and in vivo approaches in the present study.

Combating multi-drug resistant malaria parasite by inhibiting falcipain-2 and heme-polymerization: Artemisinin-peptidyl vinyl phosphonate hybrid molecules as new antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Rana, Kalpeshkumar C.; Datta, Gaurav; Asad, Mohd; Sundararaman, Srividhya; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Artemisinin-based combination therapies (ACTs) have been able to reduce the clinical and pathological malaria cases in endemic areas around the globe. However, recent reports have shown a progressive decline in malaria parasite clearance in South-east Asia after ACT treatment, thus envisaging a need for new artemisinin (ART) derivatives and combinations. To address the emergence of drug resistance to current antimalarials, here we report the synthesis of artemisinin-peptidyl vinyl phosphonate hybrid molecules that show superior efficacy than artemisinin alone against chloroquine-resistant as well as multidrug-resistant Plasmodium falciparum strains with EC<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">50<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in pico-molar ranges. Further, the compounds effectively inhibited the survival of ring-stage parasite for laboratory-adapted artemisinin-resistant parasite lines as compared to artemisinin. These hybrid molecules showed complete parasite clearance in vivo using P. berghei mouse malaria model in comparison to artemisinin alone. Studies on the mode of action of hybrid molecules suggested that these artemisinin-peptidyl vinyl phosphonate hybrid molecules possessed dual activities: inhibited falcipain-2 (FP-2) activity, a P. falciparum cysteine protease involved in hemoglobin degradation, and also blocked the hemozoin formation in the food-vacuole, a step earlier shown to be blocked by artemisinin. Since these hybrid molecules blocked multiple steps of a pathway and showed synergistic efficacies, we believe that these lead compounds can be developed as effective antimalarials to prevent the spread of resistance to current antimalarials.

Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.

Comprehensive in vitro and in silico assessment of eugenol glycoconjugates against azole and amphotericin B resistant Rhizopus spp. - Sen, Pooja; Gupta, Lovely; Chauhan, Aastha; Goswami, Lakshmi; Bhattacharya, Asish K.; Sengupta, Abhishek; Vijayaraghavan, Pooja (Molecular Biology Reports, 2025)
Background Rhizopus spp. is a major cause of mucormycosis, a severe infectious disease with high morbidity and mortality. Treatment is challenging due to rising antifungal resistance. Glycosylation is a crucial technique for enhancing the properties of phenolic compounds like eugenol. The present study aims to examine the antifungal efficacy of eugenol glycoconjugates against azole and amphotericin B-resistant Rhizopus isolates. Methods and results Out of 50 soil samples, 12 isolates belonging to Mucorales were obtained, of which 7 were identified as Rhizopus spp. via 18S ITS sequencing. Antifungal susceptibility testing (AST) revealed that all Rhizopus isolates were resistant to amphotericin B (MIC > 1 mu g/mL). Most isolates also showed resistance towards posaconazole (MIC > 1 mu g/mL) and itraconazole (MIC > 2 mu g/mL). AST of eugenol glycoconjugate (coded 6g) showed efficacy against resistant Rhizopus isolates, with MIC values ranging from 6.25 mu g/mL to 25 mu g/mL. Flow cytometry confirmed its fungicidal activity, correlating with MIC data. Compound 6g significantly reduced conidial germination within 24 h and exhibited no cytotoxicity on A549 lung cancer cells. In-silico analysis revealed a negative binding affinity of compound 6g for the spore coat protein CotH3, which could be a potential antifungal target. Conclusion Compound 6g could be an potential antifungal molecule against resistant Rhizopus spp, which requires further studies.
Keywords: Antifungals; Eugenol; Glycoconjugates; Mucormycosis; Resistance; Virulence

Cyclopropane containing triterpenoids, cycloartenone, and cycloartenol: isolation, chemical transformations, and anticancer studies - Paul, Sayantan; Mandal, Kartik; Santra, Manas K.; Bhattacharya, Asish K. (ChemistrySelect, 2025)
Cycloartenone and cycloartenol, two plant-derived triterpenoids possessing cyclopropane ring were isolated from the latex of Artocarpus heterophyllus (jackfruit). Cycloartenol was chemically modified to synthesize dihydrocycloartenol via acetylation and deacetylation methodology followed by hydrogenation. Hydroxyl group present in the cycloartenol was also employed for the nitro benzoate formation. All the isolated and synthesized compounds were assayed against MCF7 breast cancer cell line for their anticancer properties.
Keywords: Anticancer studies; Artocarpus heterophyllus; Chemical transformations; Cycloartenol; Cycloartenone